Development of sperm cryopreservation techniques in pejerrey Odontesthes bonariensis - Lichtenstein, Gabriel (2010)
The pejerrey, Odontesthes bonariensis, is being considered for aquaculture due to its high demand and market price. Reproduction and larviculture studies have demonstrated the feasibility of massive fingerling production, and techniques that prolong life and increase gamete viability can assist in the culture development of this species. In this regard, the main objective of this study was to develop freezing protocols for pejerrey sperm. For this purpose, two extenders: Ex1, a modified Mounib solution (127 mM NaHCO3, 159 mM sucrose, 0.025 g/ml reduced glutathione; pH: 8; osmolality 400 mOsm/kg) and Ex2, a saline based solution (250 mM NaHCO3, 100 mM trehalose; pH: 8; osmolality 450 mOsm/kg) were developed. Dimethyl sulfoxide (DMSO) and ethylene glycol, (EG) were added at 10% as cryoprotectants and two types of containers were used: cryovials (1 ml of volume) and French straws (0.250 ml). Cryopreservation was made without equilibration time using dry ice or liquid nitrogen. The results obtained by freezing pejerrey semen with dry ice showed that all the combinations tested were suitable because high motility indexes (among 4 or 5) and good fertility percentages (between 46% and 56%) were obtained after thawing. However, the fertilization percentage obtained with control semen was significantly higher (80%). No significant statistical differences were observed on the fertilization percentages between experimental combinations or the containers used. In the case of liquid nitrogen as freezing method, it was possible to obtain for all the combinations motility indexes among 3 or 4 after thawing. In the case of fertilization trials, similar percentages (around 80%) were found for control semen and for the majority of cryopreserved samples. However, statistically lower results (among 44%–60%) were found for Ex1DMSO (cryotubes) samples and for Ex1EG samples in both containers. In summary, the feasibility to cryopreserve pejerrey sperm was demonstrated for the first time using simple and practical protocols.